Menakar Ulang Batas Usia Perkawinan: Edukasi Hukum atas Dispensasi Kawin dan Implikasinya dalam Pencegahan Stunting di Kalangan Pelajar - Nurrahman Fajrul Sinrang; Firman Husain (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Early marriage remains an issue with negative impacts on the health and quality of the younger generation, particularly through the risk of stunting in children. This article discusses the results of a counseling session titled